Synthesis of (+)-Methyl Dihydropalustramate and of the Pyrido[1,2-a]azepine Core of Stemona Alkaloids - Mayer, Camilla; Romek, Alexandra; Bach, Thorsten (Synlett, 2015)
Starting from a readily available, enantiomerically pure 2,6-disubstituted piperidine the synthesis of pyrido[1,2-a]azepines was accomplished. Key reactions for the ring closure were a photochemically induced acyl radical addition or a SmI2-promoted ketyl radical addition to an α,β-unsaturated ester. En route to the cyclization precursor an epoxidiation/ring opening sequence led to an undesired oxazolidinone which turned out to be useful for the configuration assignment. The compound was successfully converted into (+)-methyl dihydropalustramate.
Keywords: alkaloids; cyclization; piperidines; radical reaction; total synthesis